Exploring idiosyncratic deals as a managerial tool: a bibliometric and content analysis - Irene Sánchez-Turón; Patricia Elgoibar; Claudio Cruz Cázares (Cogent Business & Management, 2025)
Idiosyncratic deals (i-deals) are voluntary, customised agreements between employees and employers that meet individual needs. As a managerial tool, i-deals have become essential in today’s work environment to attract, motivate and retain talent. This paper explores the evolution of i-deals research from its inception in 2001 to 2023. It combines a bibliometric performance analysis and science mapping of 192 articles from the Web of Science (Study 1), alongside a content analysis of the 30 most impactful publications (Study 2). Findings highlight key theoretical and methodological gaps discussed across both studies. Research remains geographically concentrated—particularly in the United States, China, and Germany—and largely confined to the human health and social work sectors, limiting its generalisability. Methodologically, the field relies heavily on quantitative approaches grounded in social exchange theory (SET) and leader-member exchange (LMX), with limited adoption of alternative theoretical perspectives or qualitative methodologies to enrich contextual understanding. Furthermore, existing studies predominantly explore ex-post i-deals from the employee perspective, often neglecting employer-initiated agreements and ex-ante negotiations. While developmental and flexibility i-deals receive considerable attention, other types and organisational settings remain underexplored. This study identifies emerging research trends and proposes future research avenues to address these gaps and broaden i-deals scholarship.